APPLICATION OF DEA METHODOLOGY IN MEASURING EFFICIENCY IN THE BANKING SECTOR - Maletić, Radojka; Kreća, Marija; Maletić, Predrag (Economics of Agriculture, 2013)
The most important aspect of any business is efficiency. The goal is to achieve greater outputs with lower inputs, or to use the available inputs to the maximum. In this paper, the use of DEA technique will be illustrated in case of measuring operation efficiency of the banking sector in Serbia, which currently has 33 banks. The efficiency of banks will be measured using two models with different input-output indicators, followed by a comparative analysis of the results using the BCG matrix. Banks are ranked according to their efficiency, and the similarities and differences that were observed in the study were commented.